Compostagem de efluente suíno como proposta de tratamento de fármacos de uso veterinário - Bohrer, Robson Evaldo Gehlen (2018)
The need for a technological solution for the treatment of swine effluents containing veterinary drugs is related to the highlight of the activity in Rio Grande do Sul, with approximately 7 million head. These effluents contribute significantly to the generation of environmental impacts to the environment. The use of veterinary drugs, especially antibiotics, often in an indiscriminate and uncontrolled way, at risk the environmental balance of the producer sites, since the animal does not completely absorb these drugs, and a fraction is excreted through feces and urine, initially accumulating in the effluent. However, the general objective of this doctoral thesis was to evaluate a composting system as a proposal for treatment of swine effluent contaminated with antibiotic residues. The work was divided in 3 parts, the first one is on the Article 1, which consists of the State of the Art review on the subject, as well as already developed alternatives for the measurement and identification of these antibiotics by means of liquid chromatography. In article 2, the decay and degradation behavior of 19 veterinary drugs during the 150 days of treatment is shown. The methodology used for composting was pilot scale with the use of eucalyptus shavings, swine effluent, which was contaminated with 19 compounds used in pig production. With this, the composting process was started (150 days). From this system parameters such as pH, temperature, humidity (were measured daily), and aliquots for microbiological evaluation (bacteria and fungi) and evaluation of drug decay were withdrawn at pre-established times. The results showed that composting had a satisfactory rate of degradation of over 90% of the studied antibiotics, proving the feasibility of composting as a treatment technique for antibiotic residues. The main objective of this paper was to identify the main microorganisms (Bacteria and Fungi) found during composting. For this, samples were collected and analyzed through the new generation sequencing technique, aiming the identification of DNA in the regions of 16S RNAr for Bacteria and ITS1 and ITS2 for Fungi. A profile was obtained, besides observing all the bacterial and fungal diversity that can be related to composting. In this diversity of microorganisms, more than 7 bacteria Phylums and 2 of Fungi were obtained, in addition to identifying more than 70 genera of bacteria and 16 fungi at different treatment times. The aim is to understand the effect and dynamism of microorganisms communities to improve composting processes, as well as to evaluate the mechanism / performance of each species in the degradation of contaminants. At the end, it was observed that composting has the potential to treat swine effluents contaminated with veterinary drugs, due to the diversity of microorganisms that are present in the process that allowed the degradation of the drugs, avoiding the direct release in environmental matrices (soil and water) reducing the environmental impacts in the producing regions, contributing to the more sustainable swine production.